1995
DOI: 10.1090/s0002-9939-1995-1246511-9
|View full text |Cite
|
Sign up to set email alerts
|

Small Mathieu group coverings in characteristic two

Abstract: Abstract. Explicit equations are given for unramified coverings of the affine line in characteristic two whose Galois groups are the Mathieu groups of degrees 11 and 12 and the automorphism group of the Mathieu group of degree 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Abhyankar used a method that relied on a characterization of the Galois groups as permutation groups while Serre used a method based on Lüroth's theorem and the invariant theory of Dickson. Later, in [3], Abhyankar obtained the Mathieu group, M 23 , as the Galois group of x 23 + tx 3 + 1 / F 2 (t). His proof was based on an idea used by Serre (in Abhyankar and Yie, [5] ) who showed that P SL (3,2) is the Galois group of x 7 + tx 3 + 1 / F 2 (t).…”
Section: The Main Resultsmentioning
confidence: 99%
“…Abhyankar used a method that relied on a characterization of the Galois groups as permutation groups while Serre used a method based on Lüroth's theorem and the invariant theory of Dickson. Later, in [3], Abhyankar obtained the Mathieu group, M 23 , as the Galois group of x 23 + tx 3 + 1 / F 2 (t). His proof was based on an idea used by Serre (in Abhyankar and Yie, [5] ) who showed that P SL (3,2) is the Galois group of x 7 + tx 3 + 1 / F 2 (t).…”
Section: The Main Resultsmentioning
confidence: 99%
“…See Section 33 of [10] for more information about the universal covering group. In their paper ( [9]), Abhyankar and Yie proved irreducibility of certain polynomials by resolving singularities of plane curves. Similarly, in Section 2, we shall prove that F~ is irreducible in k(X) [Y] by resolving singularities of a projective plane curve.…”
Section: Theorem (13) the Equation F~ = 0 Gives An Unramified Covermentioning
confidence: 99%
“…In papers [5], [8] and [9], linearization lemmas were proved and these lemmas produced some upper bounds for the relevant Galois groups. These lemmas say that a polynomial f divides a linearized polynomial A.…”
Section: Theorem (13) the Equation F~ = 0 Gives An Unramified Covermentioning
confidence: 99%
See 2 more Smart Citations